Evaluation of In vitro activity of tigecycline against multidrug-resistant clinical isolates - Livya A Wilson; Thomas S Kuruvilla (Wolters Kluwer Medknow Publications, 2023)
Introduction: Multiple drug resistance (MDR) of the bacteria is an issue across any health-care setting worldwide. This leads to prolonged hospital stay and high cost of treatment. One must be cautious to use reserve drugs such as imipenem, meropenem, colistin, polymyxin, and tigecycline. Tigecycline is a mainstay to treat emerging single or MDR pathogens. The study was conducted to assess the in vitro sensitivity of tigecycline to MDR isolates and to compare the sensitivity of Kirby-Bauer (KB) disc-diffusion method with the Epsilometer (E-test) against various MDR clinical isolates. Materials and Methods: This prospective study was done from January 2019 to 2020 on MDR isolates from clinical specimens. The isolates were tested for their antibiotic sensitivity to tigecycline by KB and E-test method to know the minimum inhibitory concentration (MIC) of tigecycline. Statistical data were analyzed by the percentage method. Results: Tigecycline showed a higher in vitro sensitivity against multidrug-resistant isolates in our study. Among the 89 MDR isolates obtained, 38 (42.7) were found to be sensitive to tigecycline by the KB diffusion and 67 (75.3) were sensitive by the E-test method. Conclusions: Tigecycline is a reserve antibiotic against MDR organisms, especially useful to treat coinfections of Gram-positive and Gram-negative superbugs. The E-test was found to be far superior to the KB method to detect in vitro activity and the results of this test will guide the clinician to judiciously use this antibiotic in their day-to-day practice.